2014
DOI: 10.1186/1471-2407-14-283
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor signalling in human breast cancer cells operates parallel to estrogen receptor α signalling and results in tamoxifen insensitive proliferation

Abstract: BackgroundTamoxifen resistance is a major problem in the treatment of estrogen receptor (ER) α -positive breast cancer patients. Although the mechanisms behind tamoxifen resistance are still not completely understood, clinical data suggests that increased expression of receptor tyrosine kinases is involved. Here, we studied the estrogen and anti-estrogen sensitivity of human breast cancer MCF7 cells that have a moderate, retroviral-mediated, ectopic expression of epidermal growth factor receptor (MCF7-EGFR).Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 59 publications
0
49
0
1
Order By: Relevance
“…To develop breast cancer therapies, targeting of ERa, which is highly expressed in approximately 70% of all breast tumors (21), is taken as a targeting molecule.…”
Section: Discussionmentioning
confidence: 99%
“…To develop breast cancer therapies, targeting of ERa, which is highly expressed in approximately 70% of all breast tumors (21), is taken as a targeting molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Compensatory relationships exist between ER and growth factor signaling, where blockage of one of them may lead to activation of the other [12,13,[16][17][18]51], and it has recently been shown that EGF-driven signaling can overrule tamoxifenmediated inhibition of MCF-7 breast cancer cell proliferation [52]. Thus, combinatorial treatment blocking both ER and growth factor signaling pathways has been suggested to be the most effective inhibition of proliferation in ER positive breast cancer cells [12,16,51,53,54].…”
Section: Treatment With Ais For 3-4 Months Suppresses Total Body Estrmentioning
confidence: 99%
“…our experiments demonstrated that EGF transitorily induced EGFR phosphorylation, and EGFR kinase inhibitor, PD153035 inhibited cell migration induced by EGF in human SiHa. It has been well proved that EGFR is an essential regulator in tumorigenesis, including tumor cell migration (Gándola et al, 2014;de Melo Maia et al, 2014;Moerkens et al, 2014). Here we presented the results demonstrating that both EGFR and its kinase activity were required for EGFinduced AQP8 expression and cell migration in human cervical cancer SiHa cells (Figure 3).…”
Section: Discussionmentioning
confidence: 61%